2010
DOI: 10.1055/s-0030-1262838
|View full text |Cite
|
Sign up to set email alerts
|

Match Running Performance and Fitness in Youth Soccer

Abstract: The activity profiles of highly trained young soccer players were examined in relation to age, playing position and physical capacity. Time-motion analyses (global positioning system) were performed on 77 (U13-U18; fullbacks [FB], centre-backs [CB], midfielders [MD], wide midfielders [W], second strikers [2 (nd)S] and strikers [S]) during 42 international club games. Total distance covered (TD) and very high-intensity activities (VHIA; >16.1 km·h (-1)) were computed during 186 entire player-matches. Physical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

43
351
9
14

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 322 publications
(417 citation statements)
references
References 44 publications
43
351
9
14
Order By: Relevance
“…Our data supports the well-established finding that wide midfielders cover more total and high-intensity running than central defenders (Buchheit et al, 2010;Carling et al, 2010;Di Salvo et al, 2009;Gregson et al, 2010). However, the present study is the first to demonstrate that both physical and technical indicators across playing position are highly dependent on the percentage ball possession, with noteworthy changes in attackers.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Our data supports the well-established finding that wide midfielders cover more total and high-intensity running than central defenders (Buchheit et al, 2010;Carling et al, 2010;Di Salvo et al, 2009;Gregson et al, 2010). However, the present study is the first to demonstrate that both physical and technical indicators across playing position are highly dependent on the percentage ball possession, with noteworthy changes in attackers.…”
supporting
confidence: 90%
“…It is well established that wide midfielders perform more high-intensity running than central defenders (Buchheit, Mendez-Villanueva, Simpson, & Bourdon, 2010;Carling et al, 2010;Di Salvo et al, 2009, Di Salvo et al, 2010Gregson, Drust, Atkinson, & Di Salvo, 2010). However, no data currently exists on the impact of ball possession on physical and technical indicators in different playing positions.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, an appropriate theoretical framework to inform threshold selection has been historically absent in the research literature, and seemingly based on early locomotor category based time-motion analyses, which were subjective in nature. For example, in the research that has examined youth and female populations there has been little justification provided for the speed zones selected, except that the thresholds were lowered to reflect the lower locomotor performance capacities of younger 44 and female cohorts. 45 One approach to has been to use mean cohort-specific physical fitness (ie, anaerobic threshold 46,47 ) or performance characteristics such as maximal sprint speed 48,49 from normative data sets to anchor player-independent (arbitrary) speed thresholds.…”
Section: Speed Thresholdsmentioning
confidence: 99%
“…Although no other studies related aerobic or anaerobic endurance tests to SSG locomotor performance, previous studies (Buchheit et al, 2010;Castagna et al, 2009;Castagna et al, 2010;Krustrup et al, 2003;Rampinini et al, 2007a;Rebelo et al, 2014) The present study assessed the variability and test-retest reliability of the 6v6-SSG for commonly used time-motion variables, including estimated metabolic power and acceleration metrics. Variability was low for total distance and metabolic power (both 4%), but higher for distance covered above high-intensity thresholds for speed, acceleration and metabolic power (8-14%).…”
mentioning
confidence: 95%
“…Besides fitness tests, time-motion analysis of both matches and SSGs in training could perhaps provide additional information about football-specific fitness. Indeed, many studies found positive correlations between aerobic fitness tests and match locomotor performance assessed as (high intensity) distance covered (Buchheit, Mendez-Villanueva, Simpson, & Bourdon, 2010;Castagna, Impellizzeri, Cecchini, Rampinini, & Alvarez, 2009;Castagna, Manzi, Impellizzeri, Weston, & Barbero Alvarez, 2010;Krustrup et al, 2003;Rampinini et al, 2007a;Rebelo, Brito, Seabra, Oliveira, & Krustrup, 2014) or estimated metabolic power (Manzi et al, 2014). However, in team sports, maximal (physical) performance is difficult to define during an actual match (Halson, 2014), as it is influenced by many factors such as player position, score line, opposition and tactics (Carling, 2013).…”
Section: Introductionmentioning
confidence: 99%